2021
DOI: 10.9758/cpn.2021.19.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Effect Neonatal Ketamine Treatment on Exploratory and Anxiety-like Behaviours in Adulthood

Abstract: Objective In this study, we evaluated the effect of neonatal ketamine exposure on anxiety-like and exploratory behaviours in adult the Balb/c and C57BL/6 strains of mice which anxiety responses are different. Methods Ketamine was administered at two different doses single dose (10, 20 mg/kg, 0.1 ml/10 g body weight, intraperitoneally) and repeated doses (10, 20 mg/kg every 240 minutes; thrice times) on the 7th postnatal day to male Balb/c and C57BL/6 mice. In adulthood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Scale bar is 10 µm. A summary graph showing average of emission ratio (FRET/CFP) in each condition n=number of cells [number of animals], Male; saline = 74 ( Ali et al, 2020 ) and ketamine = 55 ( Akillioglu et al, 2012 ), Female; saline = 61 ( Ali et al, 2020 ) and ketamine = 130 ( Akillioglu and Karadepe, 2021 ), *p<0.05 and **p<0.01, unpaired two-tailed student t-test. A scale bar indicates 25 μm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar is 10 µm. A summary graph showing average of emission ratio (FRET/CFP) in each condition n=number of cells [number of animals], Male; saline = 74 ( Ali et al, 2020 ) and ketamine = 55 ( Akillioglu et al, 2012 ), Female; saline = 61 ( Ali et al, 2020 ) and ketamine = 130 ( Akillioglu and Karadepe, 2021 ), *p<0.05 and **p<0.01, unpaired two-tailed student t-test. A scale bar indicates 25 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Both the open field test and tail suspension test have long been used to determine animals’ anxiety- and depression-like behaviors, respectively, in rodents ( Seibenhener and Wooten, 2015 ; Ueno et al, 2022 ). Specifically, the open field test has been widely used to measure the ketamine effects on anxiety-like behavior in rodents ( Guarraci et al, 2018 ; Pitsikas et al, 2019 ; Shin et al, 2019 ; Akillioglu and Karadepe, 2021 ; Yang et al, 2022 ; Acevedo et al, 2023 ). We thus measured locomotor activity and anxiety-like behavior using the open field test as carried out previously ( Shou et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…NMDAR blockade during the developmental period has previously been associated with persistent anxiety in adulthood ( Wedzony et al, 2008 ). In the EPM maze study, Akillioglu and Karadepe demonstrated that single and repetitive doses of 10 and 20 mg/kg on the 7th post-natal day increased anxiety-like behavior in adulthood ( Akillioglu and Karadepe, 2021 ). Onaolapo's study ( Onaolapo et al, 2019 ) showed that subchronic ketamine administration increased time spent in the open arm of the EPM at all doses studied (7, 15, or 30 mg/kg per day for 8 weeks), indicating that ketamine may have an anxiolytic effect.…”
Section: Discussionmentioning
confidence: 99%